2004
DOI: 10.1111/j.1365-2141.2004.04865.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of an automated procedure for the selection of effective platelets for patients refractory to random donors based on cross‐matching locally available platelet products

Abstract: Summary In 1999, we implemented an automated platelet cross‐matching (XM) programme to select compatible platelets from the local inventory for patients refractory to random donor platelets. In this study, we evaluated platelet count increments in 40 consecutive refractory patients (8·3% of 480 consecutive platelet recipients) given 569 cross‐match‐negative platelets between April 1999 and December 2001. XM was performed automatically with a commercially available immunoadherence assay. Pre‐, 1‐ and 24‐h post‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 31 publications
(26 reference statements)
3
30
0
4
Order By: Relevance
“…The significance of the area under the ROC curve is also indicating that flow cytometric platelet cross-matching is a good technique for platelet crossmatching. Rebulla et al [10] reported the same result although they used another automated technique.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The significance of the area under the ROC curve is also indicating that flow cytometric platelet cross-matching is a good technique for platelet crossmatching. Rebulla et al [10] reported the same result although they used another automated technique.…”
Section: Discussionsupporting
confidence: 65%
“…A commonly used alternative to HLA-matched platelets is the transfusion of cross-match compatible platelets [10,11]. Cross-matching compatibility has been used for identification of candidate platelet donor and may be beneficial in patients in whom refractoriness is due to HPA, so the HLA-matched platelet transfusion has no value [12].…”
Section: Introductionmentioning
confidence: 99%
“…All but 5 of the studies included in the systematic review enrolled transfusion-refractory, predominantly alloimmunized patients. Similar to the data available for HLA-selected platelets, there were limited data on mortality or hemorrhage, as no study was designed to evaluate these clinical outcomes, and there were no RCTs [84,85]. The degree of HLA alloimmunization appeared relatively stable throughout crossmatch support for the majority of patients, that is, the concern that broadening of HLA alloimmunization would result from crossmatched platelets was not substantiated.…”
Section: Summary Evidence and Rationale For Recommendationsmentioning
confidence: 84%
“…4 Istilah refrakter, 2 kali kegagalan respon terhadap transfusi trombosit, menunjukkan bahwa trombosit dari donor tidak meningkatkan kadar trombosit sesuai dengan yang diharapkan, berdasarkan jumlah trombosit yang diberikan dan estimasi volume darah pasien. 5 Trombositopenia refrakter dapat diakibatkan oleh faktor imun dan non-imun. Penyebab non-imun lebih sering menyebabkan respons pascatransfusi yang kurang baik.…”
unclassified
“…17,18 Rumus perhitungan CCI yaitu Trombositopenia refrakter didefinisikan sebagai kegagalan respons berulang terhadap transfusi trombosit 2 kali atau lebih berturut-turut. Refrakter didefinisikan sebagai nilai CCI 4,[5][6][7]5x10 9 /L pada 10-60 menit pascatransfusi dan 2,5-4,5x10 9 /L pada 18-24 jam pascatransfusi. 17 Sebanyak 30-70% pasien menjadi refrakter terhadap transfusi trombosit karena beberapa faktor, seperti demam/infeksi, koagulopati intravaskular diseminata, dan antibodi atau toksisitas terkait obat.…”
unclassified